QUALITY ASSURANCE IN TEACHER EDUCATION (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Quality became very common word nowadays. What actually quality means. It is very familiar term but its meanings and uses vary widely. In general term quality is the position of a product or a process attribute on good bad scale. It is often associated or linked with defects and deficiencies in products or process.